Kontradiksi Maklumat Pelayanan di Indonesia: Analisis Bibliometric dan Tinjauan Systematic Literatur Review - Yuliansah, Romi Ali; Pratama, Dendi Pribadi (Universitas 17 Agustus 1945 Surabaya, 2025)
his research applies a mixed-method design through Bibliometric Analysis and SystematicLiterature Review (SLR). The bibliometric analysis was conducted using VOSViewer, and datawere collected from 836 articles published between 2000 and 2024 through the Google Scholardatabase. The systematic review was managed using Covidence to filter, extract, and synthesizerelevant literature. The collected articles were classified into three groups: internationaljournals, indexed international journals, and national journals, with the majority (62%)originating from indexed international publications. The findings show that research on servicecharters in Indonesia is still fragmented and rarely integrates the three analytical dimensions:service charters, organizational effectiveness, and service evaluation. The bibliometricmapping reveals that recent studies increasingly emphasize “service standards,” “performancemeasurement,” and “organizational improvement,” yet lack comprehensive evaluationframeworks. This study concludes that the implementation of service charters in Indonesiarequires more vigorous policy enforcement, continuous evaluation, and institutionalcommitment to ensure tangible improvement in public service performance. The researchcontributes a novel analytical framework combining bibliometric mapping and systematicsynthesis to enrich theoretical and empirical understanding of service charters in the contextof public administration.